Pelatihan Persiapan Memasuki Dunia Kerja Bagi Generasi Z: untuk Keunggulan dalam Kompetisi Seleksi Karyawan - Tjahjani Prawitowati; Nurcholis Setiawan; Shinta Setia (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Z Generation has now entered the world of work, so competition for jobs is getting tighter and special advantages are needed to win the selection competition for new employees in organizations. This preparatory training for entering the world of work in community service is carried out for final semester students as prospective job seekers from generation Z. This training is one solution to increase the absorption of higher education (PT) graduates in the world of work and help companies as users of graduates to get candidates who are ready to take part in the selection. This training also provides understanding for the community, especially training participants, about how to prepare themselves to face employee selection competitions, starting from compiling application letters and curriculum vitae (CV), competency tests, interviews and how to maintain a good self-image starting from the initial entry process. the world of work, namely the recruitment selection process until the end of the employment relationship. The training stages carried out include analysis of training needs, implementation of training and evaluation of training. The results of the training show that participants have been able to recognize their own strengths and weaknesses as a basis for planning personal development, choosing the type of career and field of work as well as setting career goals.